Novel mononuclear ruthenium(ii) complexes as potent and low-toxicity antitumour agents: synthesis, characterization, biological evaluation and mechanism of action. Issue 36 (22nd March 2016) - Hu, Pengchao; Wang, Ying; Zhang, Yan; Song, Hui; Gao, Fangfang; Lin, Hongyi; Wang, Zhihao; Wei, Lei; Yang, Fang
Abstract : The ruthenium(ii ) complex, [Ru(dmb)2 (salH)]PF6 (Ru-2), is considered a potential antitumour agent that could avoid the side-effects of platinum-based anti-cancer drugs, such as cisplatin, carboplatin or oxaliplatin. Abstract : The ruthenium complex is considered a potential agent that could avoid the side-effects and chemoresistance of platinum-based anti-cancer drugs, such as cisplatin, carboplatin or oxaliplatin. In our study, three novel mononuclear ruthenium(ii ) complexes with salicylaldehyde as an ancillary ligand, [Ru(bpy)2 (salH)]PF6 (Ru-1 ), [Ru(dmb)2 (salH)]PF6 (Ru-2 ) and [Ru(phen)2 (salH)]PF6 (Ru-3 ), where bpy = 2, 2′-bipyridine, dmb = 4, 4′-dimethyl-2, 2′-bipyridine, phen = 1, 10-phenanthroline, and salH = salicylaldehyde, have been synthesized, characterized and evaluated in vivo and in vitro . We showed thatRu-2 effectively blocked DNA synthesis and induced cell apoptosis by interacting with double-stranded DNA. More significantly, Ru-2 showed excellent antitumour effects in a cellular study (IC50 values of 3.60 μM for BGC823 human gastric cancer cells in vitro ) and a xenograft model (inhibited tumour growth by 46%) at a dose of 5 mg kg −1 and exhibited insignificant hepatotoxicity and nephrotoxicity compared with a 4 mg kg −1 cisplatin-treatment. These results reveal thatRu-2 might be a potential anticancer agent that could improve on the efficacy of common anticancer therapies, such as platinum-based drugs.